PSYCHOLINGUISTIC STUDY OF EMOTIONALPSYCHOLOGICAL STATES - Muhammadjon Mamajonov (Western European Studies, 2024)
This text explores the significant influence of the speaker's attitude towards reality, the interlocutor, and the speech situation on the expression of emotions in communication. It examines how emotional states manifest through physiological, psychological, and linguistic signs, emphasizing the interplay between direct and conceptualized expressions of emotions. Using examples from Uzbek literature and daily interactions, the study illustrates the crucial role of context, relationships, and situations in shaping emotional communication. The findings highlight the complexity of emotional expression and the importance of understanding both verbal and non-verbal cues to achieve effective communication
Keywords: emotion; communication; speech context